Therapeutic Potential of Vagus Nerve Stimulation for Inflammatory Bowel Diseases - Bonaz, Bruno; Sinniger, Valérie; Pellissier, Sonia (Frontiers in Neuroscience, 2021)
The vagus nerve is a mixed nerve, comprising 80% afferent fibers and 20% efferent fibers. It allows a bidirectional communication between the central nervous system and the digestive tract. It has a dual anti-inflammatory properties via activation of the hypothalamic pituitary adrenal axis, by its afferents, but also through a vago-vagal inflammatory reflex involving an afferent (vagal) and an efferent (vagal) arm, called the cholinergic anti-inflammatory pathway. Indeed, the release of acetylcholine at the end of its efferent fibers is able to inhibit the release of tumor necrosis factor (TNF) alpha by macrophages via an interneuron of the enteric nervous system synapsing between the efferent vagal endings and the macrophages and releasing acetylcholine. The vagus nerve also synapses with the splenic sympathetic nerve to inhibit the release of TNFalpha by splenic macrophages. It can also activate the spinal sympathetic system after central integration of its afferents. This anti-TNFalpha effect of the vagus nerve can be used in the treatment of chronic inflammatory bowel diseases, represented by Crohn’s disease and ulcerative colitis where this cytokine plays a key role. Bioelectronic medicine, via vagus nerve stimulation, may have an interest in this non-drug therapeutic approach as an alternative to conventional anti-TNFalpha drugs, which are not devoid of side effects feared by patients.